Studies of thermal stability of epoxy compounds for glass-fiber pipes - Karandashov, Oleg; Avramenko, Viacheslav (Lviv Politechnic Publishing House, 2017)
Досліджено термічну стабільність різних епоксидних сполук, призначених для використання в певних температурних діапазонах. Визначено вплив температури на фізико-механічні властивості труб, зокрема, їх руйнівне напруження при осьовому розтягненні і залежність від хімічної природи затвердника.

Thermal stability of different epoxy compounds designed for their use in certain temperature ranges has been studied. Effects of temperature are reported upon physico-mechanical properties of pipes, in particular, their failure stress under axial tension and their dependence on chemical nature of the solidifier.
Дослідження термостабільності епоксидних сполук для скловолоконних труб
Keywords: затвердник; руйнівне напруження; термостабільність; полімерна сполука; наповнювач; solidifier; failure stress; thermal stability; polymer compound; filler